Can the medullary diameter/cortical thickness ratio be a predictor of diaphyseal fracture in elderly patients treated with cephalo-medullary nail for proximal femur fractures? A retrospective cohort study on 488 patients - Canton, Gianluca; Nassiz, Pamela; Ratti, Chiara; De Luca, Alessandro; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2023)
Background and aim of the work: Diaphyseal femoral fracture occurring distal to the CM nail tip is an infrequent complication that presents some similarities with periprosthetic hip fractures. The purpose of this study is to evaluate the correlation between medullary diameter (MD) and cortical width (CW) ratio, a known risk factor for periprosthetic fracture, with the occurrence of diaphyseal fracture distal to the nail tip.Research Design and Methods: Study population included patients > 65 years old treated with short CM nail for proximal femur fractures (PFF) at the Cattinara Hospital-ASUGI of Trieste (Italy) Orthopedics and Traumatology Unit between July 2014 and May 2018. Latest follow-up X-rays were evaluated to identify diaphyseal fracture occurrence. We recorded type of trauma, time lapse between CM nailing and diaphyseal fracture and calculate the MD/CW ratio on intra-operative X-rays. Data were analyzed to find out a correlation with the occurrence of diaphyseal fractures.Results: The study population counted 488 patients. Diaphyseal fracture occurred in 14 cases (2.9%, F:M ratio 6:1, mean age 87 years), at mean 26.07 months after CM nailing. The MD/CW ratio identified a trend of increased risk of diaphyseal fractures as the ratio increases (OR 4.51; CI 0.826-24.642) although the correlation does not reach statistical significance (p 0.082).Conclusions: The results of the present study demonstrate a trend towards a higher risk of diaphyseal fracture as the MD/CW ratio increases, although the association did not reach statistical significance due to the small number of events.